An Analysis of the Capital Structure of the Hungarian Corporate Sector - Szemán, Judit (Theory, Methodology, Practice – Review of Business and Management, 2011)
It is well-known that in the 90’s enormous changes occurred in the structure of the Hungarian economy, which influenced the tradition of corporate financing. In line with political changes, foreign-owned companies appeared that adopted the financing strategies of their mother companies. In addition to the ownership structure, there were significant changes in the sectorial structure of the economy. The share of the agricultural sector has decreased; the share in employment and in GDP has shifted in favour of machinery and services (especially telecommunication and financial services). This paper examines the whole corporate branch divided into sectors, showing how company capital structure changed in Hungary between 1992 and 2003, and contains a short analysis about the period 2004-2010. One of the most important findings is that the corporate capital structure has only secondary importance; companies make primarily production, market and investment decisions, and the financing decisions are the effects of these primary decisions. This secondary manner is typical in Hungary and in the other transition economies, where the financial culture is still at a low level (although it has developed by large steps in recent years), the financial markets are underdeveloped, and companies traditionally prefer to use internal sources rather than loans with interest and principal payment obligations. This study investigates theories of capital structure against the behaviour of the Hungarian corporate sector.